Financial frictions and the monetary transmission mechanism: theory, evidence and policy implications - Charles Bean; Jens D. J. Larsen; Kalin Nikolov (European Central Bank (ECB), 2002)
This paper provides a brief survey of the role of financial frictions in the monetary transmission mechanism. After noting some of the key stylised facts that any model of the transmission mechanisms must be consistent with, we discuss both the classical interest rate channel and the credit and bank lending channels of monetary transmission. We then review the empirical evidence relating to the relative importance of these channels. Finally we consider what impact the presence of significant financial frictions might have on the conduct of monetary policy
Keywords: E52; E58; E44; 330; bank-lending channel; credit channel; monetary policy; transmission mechanism